Requirements management tools / Ameran Jaffar - Ameran, Jaffar (2004)
This dissertation is a research on project management tools specifically in the area of requirements management. The dissertation begins with an introduction on requirements engineering phase in a typical software development project. Subsequently the problems pertaining to requirements engineering are discussed. The reasons for failures on software development project due to lack of requirements are also discussed. We had conducted a questionnaire session to system analysts from fifteen local organizations. We found that even most of them recognize the problems on requirements but none are practising known requirements management methodology. We had reviewed a few requirements management methodologies and one method has been selected for a case study. A case study was conducted to find that methodology effectively improve the quality of the requirements specification. We also conduct a study on requirements management tools. This is to find out a model for more applicable tools, hence a system analyst or software engineer can practically use it. The enhanced model for the requirements methodology has been proposed. The proposed tools shall be simpler to that available in the industries and it offers interfacing with the tools normally used by our analyst such as Microsoft Word and Visual Modeler for Unified Modeling Language (UML). Hopefully, once the tool is completed, it will help our software industry. A prototype has been developed and demonstrated to the system analysts who participated in the previous case study. They have been given one week to test and give feedback to further enhanced the prototype. Some of the enhancements have been immediately modified but others may need more time.